K- Popfication in Viral Marketing: Increasing Brand Awareness and Purchasing Decisions of MSMEs - Maulina, Dwi; Pasaribu, Popy Novita; Indupurnahayu, Indupurnahayu (Universitas Ibn Khladun Bogor, 2024)
The K-pop phenomenon has become one of the significant global culture trends, impacting not only the entertainment industry but also various aspects of marketing. This study aims to explore the impact of K-pop elements in viral marketing strategies on MSMEs in Indonesia, especially in increasing brands awareness and consumer purchasing decisions. The sample formed of 75 respondents who were selected using purposive sampling, with criteria MSME's customers on on line shopping. Data analysis using Structural Equation Modeling (SEM) with the help of Smart PLS 4.1. The research results shows that K- Popfication has been a significant influence on increasing brands awareness and purchasing decisions. This indicates that marketing strategies that integrate elements of K-Pop culture are effective in increasing brands awareness and encouraging consumers to make purchases. In contrast, neither buzz marketing nor viral marketing showed a significant influence on brands awareness and purchasing decisions in the context of this research. These findings provide important insight that in an effort to increase visibility and sales, K- Popfication has greater potential than other marketing strategies that do not involve elements of popular culture such as K-Pop.